The Integration of Business Model, Curriculum and Core Business Operation for Commerce Laboratory - Maramis, Diana Roweina Susana; Dua, Iyam L; Kolondam, Arifmanuel; Mangolo, Mikhael Credo Samuel; Joroh, Adelaida (Asian Journal of Logistics Management, 2023)
Laboratories in vocational higher education have an important role in complementing the learning process for students to gain an optimum learning experience, especially in Vocational Colleges, where the quality of students is expected to possess skills and expertise that are applicable in the workplace. Laboratories in vocational higher education have many important roles in students' learning experiences, especially in the area where students are able to sharpen their practical skills by directly applying all the theories they have learned. This provides students with the opportunity to optimize and even master various skills relevant to their chosen field of study or profession. The optimization of student learning includes making laboratories function as real business entities, so that students can gain learning experiences in conditions that closely resemble those in the industry. One of the efforts to develop the potential of resources owned by a laboratory is to maximize the business potential of each laboratory, especially Commerce Laboratories. Integration between the business process and the learning process in commerce laboratories is necessary to ensure that both aspects run smoothly, rather than being misaligned. When the laboratory functions as a business entity, it can achieve maximum profit while simultaneously providing practical learning experiences to students.